The tragedy of Macbeth - "Shakespeare, William" (Sweet cherry publishing: China, 2013)
Macbeth is one of the darkest tragedies of William Shakespeare. The play revolves around a power-hungry Scottish lord, Macbeth, and his lady, who conspire to kill King Duncan. After Duncan's death, Macbeth ascends the throne, only to be consumed by guilt, panic and paranoia, which ultimately lead him to his doom. This short narrative version of the play has been suitably adapted to help introduce the story to young readers
Keywords: Adaptations Juvenile literature